Eating flowers for healthy living - Singh, Babita; Majumder, Jayoti; Perinben, Sellam; Rai, Puja; Kumar, Ramesh (Indian Horticulture, 2015)
Edible flowers are rich in essential oils, which can help build up electrical energy in the body and also provide nutrients and healing properties. Today, many restaurant chefs and innovative homecooks garnish their entries with flower blossoms for a touch of elegance. The secret to success when using edible flowers is to keep the dish simple, do not add to many other flavours that will over power the delicate taste of the flower.